Nano-micron pore channel composite perovskite electrode material, preparation method and application in solid oxide fuel cell

By using nano-scale soft template and electrospinning technology to prepare composite perovskite electrode materials with micro-nano-scale channel structures in SOFC, the problems of local pressure increase and gas release difficulties caused by high oxygen partial pressure are solved, and the long life and high performance of the electrode are achieved.

CN119601675APending Publication Date: 2025-03-11DATANG DONGBEI ELECTRIC POWER TESTING & RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411434287.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

During long-term operation, the solid oxide fuel cell (SOFC) anode causes interface layering due to high oxygen partial pressure, resulting in increased local pressure and difficulty in releasing gas, which in turn causes anode attenuation.

Method used

Nanofiber precursors were prepared by electrospinning using nanoscale soft templates and laser sintered to obtain composite perovskite electrode materials with micro-nano-scale pore structures to improve the exposure probability of pores, reduce local pressure, and ensure smooth gas release.

Benefits of technology

By constructing a composite perovskite electrode material with a multi-stage pore structure, the pore exposure probability is significantly improved, local pressure is reduced, the service life of the SOFC electrode is extended, the anode attenuation is avoided, and the stability and performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601675A_ABST
    Figure CN119601675A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-micron pore channel composite perovskite electrode material, a preparation method thereof and application of the nano-micron pore channel composite perovskite electrode material in a solid oxide fuel cell, and belongs to the technical field of inorganic material synthesis. The invention solves the problem of insufficient pore channel exposure rate of the existing solid oxide fuel cell electrode material. Nanoscale polystyrene microspheres are used as a soft template, metal salt is combined, a nanofiber precursor is prepared through an electrostatic spinning method, then sintering is carried out, and the composite perovskite electrode material of a micron-nanoscale pore channel structure is obtained. According to the preparation method provided by the invention, the polystyrene microspheres are subjected to laser sintering, so that spherical nano pore channels are reserved in the fibers, the pore channel exposure probability is further improved, the battery performance is more stable, and moreover, the preparation method provided by the invention can realize controllable synthesis of a composite perovskite electrode material, so that large-scale stable preparation of high-activity electrodes is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of inorganic material synthesis, and relates to a method for synthesizing a nano-scale composite perovskite with a multi-level pore structure, and in particular to a nano-micron pore composite perovskite electrode material, a preparation method thereof, and an application in a solid oxide fuel cell. Background Art

[0002] With the transformation of energy structure and the background of "dual carbon", the demand for clean, low-carbon and efficient energy is becoming increasingly strong. Solid oxide fuel cells (SOFC) have broad application prospects due to their high efficiency, wide adaptability, pollution-free, all-solid structure, and no need for precious metal catalysts. They can not only solve the problem of clean utilization of traditional fossil energy, but also promote the development of green environmental protection, which is of great significance to the optimization of energy structure. SOFC can be used in small household cogeneration systems, distributed power generation, transportation and other fields. Among them, large-scale coal gasification fuel cell power generation technology (IGFC) with near-zero CO2 emissions is a power generation system that combines integrated coal gasification combined cycle power generation (IGCC) with high-temperature solid oxide fuel cells or MCFC. It has higher power generation efficiency and low CO2 capture cost, which is a fundamental transformation technology for coal power generation.

[0003] At present, there are still many problems in the practical application of SOFC. It is urgent to carry out relevant basic research on applications, master the design and manufacturing process of long-life and highly reliable fuel cell stacks, and develop high-efficiency, long-term stable operation high-power systems. Among them, the attenuation of the SOFC anode has a greater impact on the overall performance. The main reason for the impact is that during long-term operation, the high oxygen partial pressure causes the interface stratification of the anode and the electrolyte film. Therefore, it is urgent to design electrodes with porous electrode structures to reduce local pressure and ensure smooth gas release.

[0004] The spinning diameter of electrospinning can range from nanometers to micrometers. Electrospinning is to place a polymer solution (melt) in a high-voltage electrostatic field. Under the action of an external electric field, the polymer solution (melt) flows and refines. Different from other spinning technologies, electrostatic interactions lead to the stretching of the polymer jet, and the diameter of the nanofibers decreases when the solvent evaporates. Since the nanofibers overlap with each other, a large number of pores are formed. The continuous fiber network can be used as a permeation support to form a three-dimensional porous nanostructure. The overall microstructure of the electrode is optimized. The specific surface area of ​​the nanofiber material is large, which increases the three-phase boundary reaction active sites of oxygen, is conducive to the transport of carriers and gases, and promotes the oxygen reduction reaction. Therefore, the nanofiber-based electrode improves the electrochemical performance of the single cell. However, as the application scenarios of solid fuel cells become more and more extensive, the requirements for their performance are also getting higher and higher. Although the nanofiber-based electrode prepared by electrospinning contains pores, the exposure probability is limited, and the gas cannot be discharged smoothly. In some aspects, it can no longer meet the use of SOFC. In order to further increase the probability of pore exposure, the soft template method is used to construct an integrated electrode with a micron-nano multi-level pore structure to achieve controllable synthesis of composite perovskite electrodes. Summary of the invention

[0005] The present invention provides a nano-micrometer pore composite perovskite electrode material and a preparation method thereof and an application in a solid oxide fuel cell in order to further improve the pore exposure probability of a solid oxide fuel cell electrode material, thereby reducing local pressure, ensuring smooth gas release, and avoiding anode attenuation. The present invention uses a nanometer-scale soft template to prepare a nanofiber precursor by an electrostatic spinning method, and then obtains a composite perovskite electrode material with a micrometer-nanometer pore structure by laser sintering. The material can be used to prepare a cathode of a solid oxide fuel cell.

[0006] In order to achieve the above purpose, the following technical solutions are adopted:

[0007] One of the purposes of the present invention is to provide a method for preparing a nano-micron pore composite perovskite electrode material, comprising:

[0008] (1) adding a metal salt to a spinning solvent, adding polyvinyl pyrrolidone, stirring to obtain a mixed sol, and then adding polystyrene microspheres, stirring to obtain a precursor sol;

[0009] (2) The precursor sol is loaded into a syringe, which is fixed to a spinning machine. After the spinning parameters are set, spinning is started. After the spinning is completed, the obtained composite fiber film green body is removed from the drum, and then dried, laser sintered, and cooled to obtain a nanofiber cooked body, i.e., a nano-micron pore composite perovskite electrode material.

[0010] In further limitation, the metal salt in (1) comprises lanthanum nitrate, strontium nitrate, cobalt nitrate, iron nitrate, cerium nitrate and gadolinium nitrate.

[0011] It is further defined that the molar ratio of lanthanum, strontium, cobalt, iron, cerium and gadolinium in the metal salt is 0.6:0.4:0.8:0.2:0.8:0.2.

[0012] It is further defined that the spinning solvent in (1) is one of a mixed solution of N,N-dimethylformamide and water, a mixed solution of dimethylacetamide and acetone, N,N-dimethylformamide, dimethylacetamide, and tetrahydrofuran.

[0013] It is further defined that the amount of spinning solvent used in (1) is 1 to 50 mL.

[0014] It is further defined that the amount of polyvinyl pyrrolidone used in (1) is 0.1 to 5 g.

[0015] It is further defined that the diameter of the polystyrene microspheres in (1) is 50 to 200 nm.

[0016] Further, the spinning parameters in (2) are: the distance between the syringe needle tip and the roller is 18 cm, the positive and negative voltage difference is 15 kV, and the liquid pushing speed is 0.3 mL·h -1 .

[0017] It is further defined that the laser sintering method in (2) is to lay the composite fiber film green body flat on the sample table, turn on the power, adjust the laser intensity to 90% of the total intensity, use line scanning as the scanning method, the number of laser scans per millimeter is 25, the laser scanning speed is 100 mm / min, the height from the light source to the green body is 20 mm, and scan continuously for 6 times to complete the sintering.

[0018] The second object of the present invention is to provide a nano-micron pore composite perovskite electrode material obtained by the above preparation method.

[0019] Further defined, the chemical formula of nano-microporous composite perovskite electrode material is La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ ;

[0020] Further defined, δ is the oxygen vacancy concentration, 3-δ ranges from 0 to 3, and 2-δ ranges from 0 to 2.

[0021] The third object of the present invention is to provide an application of the above-mentioned nano-micron pore composite perovskite electrode material as a cathode in a solid fuel cell.

[0022] Further defined, the application method is:

[0023] (1) preparing an anode support by a tape casting method;

[0024] (2) preparing an electrolyte layer by screen printing, and then performing primary sintering and secondary sintering on the electrolyte layer;

[0025] (3) preparing the barrier layer by screen printing and then sintering the barrier layer;

[0026] (4) preparing a cathode by screen printing and then sintering the cathode;

[0027] (5) Assembling the anode support, electrolyte layer, barrier layer, and cathode to obtain a solid oxide fuel cell.

[0028] It is further defined that the anode support is nickel oxide / yttria-stabilized zirconia, the electrolyte layer is yttria-stabilized zirconia, and the barrier layer is gadolinia-doped cerium oxide.

[0029] It is further defined that the primary sintering temperature of the electrolyte layer is 1100°C, the secondary sintering temperature is 1380°C, the barrier layer sintering temperature is 1100°C, and the cathode sintering temperature is 900°C.

[0030] The beneficial effects of the present invention are:

[0031] The present invention utilizes a soft template method to construct a composite perovskite electrode material containing a micron-nano multi-level pore structure. The specific process is: using nano-scale polystyrene microspheres as soft templates, preparing nanofiber precursors through an electrostatic spinning method, and then laser sintering to obtain a composite perovskite electrode material with a nano-micron pore structure. Compared with the prior art, the present invention realizes the preparation of an electrode material with a large specific surface area. Nanofibers are stacked on each other to form micron-scale pores. The polystyrene microspheres can volatilize after laser sintering, and spherical nanopores are left inside the fibers after sintering. This nano-micron multi-level pore structure further increases the probability of pore exposure, which is beneficial to further reduce local pressure when the material is used as a cathode, ensure smooth gas release, and thus avoid anode attenuation; in addition, the electrode material provided by the present invention is a composite perovskite, and the material itself has good electrical conductivity, catalytic activity, thermal stability, etc., and the preparation method of the present invention can increase the pore exposure rate, thereby making the use of solid fuel cells more stable; in addition, by adjusting the reaction parameters, the controllable synthesis of the composite perovskite electrode material can be achieved, thereby realizing the large-scale stable preparation of high-activity electrodes. Compared with the prior art, the present invention also has the following advantages:

[0032] (1) The preparation method provided by the present invention can uniformly mix perovskite and oxide in microstructure through electrospinning technology to form a composite perovskite material with uniform microstructure, thereby avoiding abnormal particle growth due to structural inhomogeneity during sintering and significantly improving the uniformity of the composite perovskite particles. The perovskite material is grown in situ on the surface or inside of the nanofibers obtained by electrospinning through chemical reaction, so that the growth position and morphology of the perovskite can be precisely controlled, thereby realizing the controllable preparation of a composite structure of micron-nano multi-level pores.

[0033] (2) The preparation process provided by the present invention involves a laser sintering step. The laser sintering has high precision and can realize accurate sintering of electrospinning green sheets. The diameter of the laser beam is very small, usually between tens of microns and hundreds of microns. Therefore, local sintering of the nanofiber green sheets can be realized, thereby obtaining a high-precision three-dimensional structure. Moreover, since laser sintering is to scan the surface of the material with a laser beam with high energy density, so that the material absorbs the laser energy and heats up to above the melting point, the material melts and bonds together at high temperature to complete sintering, so the sintering speed is fast, and the sintering of the electrospinning green sheets can be completed in a short time, greatly improving production efficiency and shortening the production cycle. Laser sintering materials have strong adaptability. For electrospinning green sheets, laser sintering can select appropriate laser parameters and sintering processes according to different material properties and requirements to realize sintering of different materials. Laser sintering can realize the control of the microstructure of the electrospinning green sheets. By adjusting the laser parameters and sintering process, the melting degree and bonding method of the powder material can be controlled to realize the control of the fiber porosity and pore size. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the preparation process of the composite perovskite electrode material of Example 1;

[0035] Figure 2 This is a digital photo of the green body of the PVP-based composite fiber film prepared in Example 1;

[0036] Figure 3 This is a scanning electron image of the PVP-based composite fiber film green body prepared in Example 1;

[0037] Figure 4 The La prepared in Example 1 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 X-ray diffraction pattern of the nanofiber raw material;

[0038] Figure 5The La prepared in Example 1 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 Scanning electron image of the nanofiber blank;

[0039] Figure 6 The power-voltage-current curve of the solid oxide fuel cell assembled in Example 1;

[0040] Figure 7 The voltage-time curve of the solid oxide fuel cell assembled in Example 1;

[0041] Figure 8 The La prepared in Example 2 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 X-ray diffraction pattern of the nanofiber raw material;

[0042] Fig. 9 The La prepared in Example 2 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 Scanning electron image of the nanofiber blank;

[0043] Fig.10 The power-voltage-current curve of the solid oxide fuel cell assembled in Example 2;

[0044] Fig.11 The La prepared in Comparative Example 1 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 @X-ray diffraction pattern of SiO2 nanofiber raw material;

[0045] Fig.12 is the X-ray diffraction pattern of the SiO2 microsphere template in Comparative Example 1;

[0046] Fig.13 This is the power-voltage-current curve of the solid oxide fuel cell assembled in Comparative Example 1. DETAILED DESCRIPTION

[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0048] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0049] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0050] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0051] Example 1

[0052] Electrode material preparation

[0053] (1) According to the stoichiometric ratio, a certain amount of lanthanum nitrate (0.3169 g), strontium nitrate (0.1032 g), cobalt nitrate (0.0710 g), iron nitrate (0.3943 g), cerium nitrate (0.0019 g) and gadolinium nitrate (0.0054 g) were weighed and added to 10 mL of N,N-dimethylformamide (DMF). After the nitrate was completely dissolved, 1.05 g of polyvinyl pyrrolidone (PVP, molecular weight 1300000) was added, and the mixture was stirred at 200 rpm for 24 h at room temperature to obtain a uniform reddish brown mixed sol. Then, 0.026 g of polystyrene microspheres (PS) with a diameter of 200 nm were added, and the mixture was magnetically stirred at 200 rpm for 12 h to obtain a precursor sol.

[0054] Among them, the polystyrene microspheres are prepared in the laboratory. The specific method is as follows: the polystyrene microspheres are prepared from styrene (Aldrich Company, purity>99%), potassium persulfate (KPS, Aladdin Company, purity>99%) is used as a polymerization initiator, polyvinyl pyrrolidone (PVP, Aldrich Company, molecular weight of 29000) is used as a surfactant, the mass ratio of PVP to styrene is 1:20, and the mass ratio of KPS to styrene is 1:100. PVP is dissolved in 50mL of cyclohexane, and potassium persulfate is dissolved in 50mL of ethanol-water solution (the volume ratio of ethanol to water is 10:4). Styrene and the dissolved polymerization initiator are poured into a reactor, nitrogen is introduced into the reactor to remove oxygen therein, the temperature is increased to 70°C, and then the dissolved PVP solution is added to the reactor. The polymerization reaction is carried out under reflux condensation and 200rpm for 24 hours. After the reaction, the product is repeatedly washed with ethanol to obtain polystyrene microspheres.

[0055] (2) The precursor sol was loaded into a syringe with a volume of 10 mL, a needle length of 25 mm, and an inner diameter of 0.61 mm, and fixed to the spinning machine. The spinning parameters were set: the distance between the syringe needle tip and the contact surface of the roller was adjusted to 18 cm, the positive and negative voltage difference was 15 kV, and the liquid pushing speed was 0.3 mL·h -1 After spinning is completed, the collected PVP-based composite fiber film green body in the form of non-woven fabric is removed and dried in a vacuum drying oven at 80°C for 24 hours;

[0056] (3) The dried PVP-based composite fiber film green body was laid flat on the sample table with a thickness of 2 mm and an area of ​​15×15 mm. The power was turned on and the laser intensity was adjusted to 90% of the total intensity. The scanning mode was line scanning. The number of laser scans per millimeter was 25. The laser scanning speed was 100 mm / min. The height from the light source to the green body was 20 mm. The scanning was performed continuously for 6 times to complete the sintering. The organic component PVP in the composite fiber film green body was removed during the sintering process. After the sintering was completed, it was naturally cooled to room temperature to obtain La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 Nanofiber preform, preparation process as Figure 1 shown.

[0057] Figure 2 This is a digital photo of the green body of the PVP-based composite fiber film prepared by electrospinning in Example (2). Figure 2 It can be seen that the surface of the green film is uniform and smooth, and is light yellow; Figure 3This is a scanning electron microscope (SEM) image of the PVP-based composite fiber film embryo. Figure 3 It can be seen that the composite fiber film green body is composed of a large number of long and uniform nanowires stacked together, and the single fibers are stacked crosswise to form a porous network structure. The average fiber diameter ranges from 150 to 250 nm. Figure 4 This is the X-ray diffraction diagram of the nanofiber raw material. It can be seen that the composition of the fiber is La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 , no impurities; Figure 5 is a SEM picture of the nanofiber blank prepared in this example. Figure 5 It can be seen that the surface of the nanofibers is smooth, slender, continuous and uniform, and the filamentous fibers are stacked disorderly with each other to form a porous and continuous micron-pore network microstructure; in addition, the fibers shrink more after high-temperature sintering, and the fibers have a hollow porous structure, which can provide a higher specific surface area and a larger porosity, providing more channels for effective charge transfer and carrier transport in electrode polarization reactions, and also providing a large number of high-quality pathways for the transmission of oxygen.

[0058] Preparation of solid oxide fuel cells

[0059] (1) Preparation of nickel oxide / yttria-stabilized zirconia anode support (NiO / 8 mol% YSZ) by tape casting

[0060] Select agate grinding balls, 150g of balls with a diameter of 10mm, and 150g of balls with a diameter of 6mm, weigh 240g of yttria-stabilized zirconia (8mol% YSZ), 360g of NiO, and 22g of graphite powder, and add them to a ball mill with a capacity of 1L in this order, pour 300mL of anhydrous ethanol into the ball mill and let it stand for 20min, run 15 cycles at 300rpm and 80min / cycle, take out the material and place it in an environment to dry, pass through a 100-mesh sieve, grind the unscreened powder with a pestle until it is completely sieved, and the pre-made powder is prepared;

[0061] Weigh 530g of pre-made powder and pour it into a ball mill, take 20g of polyvinyl pyrrolidone (PVP, K29-32, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) in a beaker, pour 300mL of anhydrous ethanol into the beaker and stir it magnetically at 200rpm until the solution is clear, then pour it into the ball mill, pour 80mL of anhydrous ethanol into the beaker, shake it slightly and pour it into the ball mill, let it stand for 3-5min, put it into the ball mill and run it for 10 cycles at 300rpm and 80min / cycle, then add 40g of polyvinyl butyral (PVB, MW70000-100000, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), continue to run for 20 cycles at 300rpm, then add 23g of polyethylene glycol (PEG-400, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and 23g of dibutyl phthalate and run it for 15 cycles, and the ball milling is finished;

[0062] The ball-milled casting slurry was poured into a beaker, placed in a vacuum defoamer, and operated at 60 rpm for 30 min. The scraper height of the casting machine was adjusted to 2.00 mm. The defoamed slurry was poured into the groove of the casting machine, and the casting machine was started. The casting rate was controlled to be 0.50 cm / s. After the casting was completed, the heating was turned on and the drying temperature was adjusted to 50°C. After drying, a NiO / 8 mol% YSZ anode support was obtained;

[0063] (2) Preparation of yttria-stabilized zirconia electrolyte layer (YSZ) by screen printing

[0064] 8 mol% YSZ powder (50 g) was added to an organic binder (6 g ethyl cellulose dissolved in 94 g pine alcohol), and ground using an agate mortar to fully mix the YSZ powder and the organic binder to finally form a uniform and stable electrolyte slurry with certain fluidity;

[0065] The electrolyte layer is printed on the anode support, and the electrolyte slurry is passed through a 300-mesh polyester screen using a rubber scraper. After printing, the YSZ film is blown dry in a 60°C blast oven. The prepared NiO-YSZ / YSZ double-layer structure is sintered at 1100°C for 24 hours and then at 1380°C for 24 hours to remove the residual organic components in the YSZ electrolyte layer, densify the electrolyte membrane, and obtain an anode support / electrolyte composite sheet;

[0066] (3) Preparation of gadolinium oxide-doped cerium oxide barrier layer (GDC) by screen printing

[0067] Gadolinium oxide doped cerium oxide powder (50 g) was added to an organic binder (6 g ethyl cellulose dissolved in 94 g pine alcohol), and ground using an agate mortar to fully mix the GDC powder and the organic binder to finally form a barrier layer slurry with certain fluidity, uniformity, and stability;

[0068] The barrier layer was printed on the electrolyte layer. The barrier layer slurry was passed through a 300-mesh polyester screen using a rubber scraper. After printing, the GDC membrane was dried in a 60°C blast oven and sintered at 1100°C for 12 hours to obtain the barrier layer.

[0069] (4) Preparation of cathode layer (La) by screen printing 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 )

[0070] The La obtained in this example 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 The powder (50 g) was added to an organic binder (6 g ethyl cellulose dissolved in 94 g pine alcohol), and ground using an agate mortar to fully mix the high entropy perovskite powder and the organic binder to finally form a cathode slurry with certain fluidity, uniformity, and stability;

[0071] The cathode slurry was passed through a 300-mesh polyester screen using a rubber scraper. After printing, it was dried in a 60°C blast oven and then sintered at 900°C for 12 hours to obtain a cathode.

[0072] (5) Finally, the anode support, electrolyte layer, barrier layer, and cathode are assembled into a solid oxide fuel cell.

[0073] Hydrogen and oxygen were introduced into the anode and cathode of the solid oxide fuel cell, respectively, and the battery was tested at 800°C and 700°C, respectively.

[0074] Figure 6 is the La prepared in this example. 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 The power-voltage-current curve of the assembled solid oxide fuel cell. It can be seen from the figure that at 800°C, the maximum power of the battery is 0.98W·cm -2 .

[0075] Figure 7 The voltage-time curve of the solid oxide fuel assembled in this example, at a constant current of 0.5 A·cm-1 The discharge was carried out in the mode, 3% H2O-97% H2 was introduced into the anode, and air was introduced into the cathode. It can be seen from the figure that within 100 hours, the electrolysis voltage of the battery did not decay, indicating that the La prepared in this embodiment 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 As cathode, the battery has good stability.

[0076] Example 2

[0077] The difference between this embodiment and embodiment 1 is that the diameter of the polystyrene microspheres (PS) added in (1) is 100 nm, the molecular weight of PVP used in the preparation of polystyrene microspheres is 8000, the mass ratio of PVP to styrene is 1:10, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0078] The crystal structure of the nanofiber blank obtained in this example was characterized, and the XRD results are as follows: Figure 8 As shown, the results show that the composition of the nanofiber raw material is La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 , without any impurities.

[0079] Fig. 9 This is the SEM picture of the nanofiber blank obtained in this example. Fig. 9 It can be seen that the fibers are obviously broken and cannot be stacked together well. The micron-scale porous network microstructure disappears, resulting in a decrease in the fiber specific surface area, which is not conducive to improving battery performance.

[0080] Fig.10 The La prepared in this example 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 The power-voltage-current curve of the assembled solid oxide fuel cell shows that at 800°C, the maximum power of the battery is 0.76 W·cm -2 , which is significantly smaller than that in Example 1.

[0081] Comparative Example 1

[0082] The difference between this comparative example and Example 1 is that in (1), polystyrene microspheres (PS) are not added, but silica microspheres (SiO2) with a diameter of 200 nm are added instead, and the remaining process steps and parameter settings are the same as those in Example 1.

[0083] The crystal structure of the nanofiber blank obtained in this example was characterized, and the XRD results are as follows: Fig.11 As shown, the results show that the composition of the nanofibers is La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 @SiO2, however, the XRD test of SiO2 template alone showed the following results: Fig.12 As shown, it can be seen that SiO2 is amorphous. Therefore, SiO2 still exists in the sample, the impurity phase cannot be removed, and because SiO2 is not conductive, it is not conducive to electron transmission, which will lead to a decrease in battery performance.

[0084] Fig.13 The La prepared in this example 0.6 Sr 0.4 Co 0.8 Fe 0.2 O3@Ce 0.8 G 0.2 O 0.19 @The power-voltage-current curve of the solid oxide fuel cell assembled by SiO2. It can be seen from the figure that at 800℃, the maximum power of the battery is 0.64W·cm -2 , which is significantly smaller than that in Example 1.

[0085] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a nano-microporous composite perovskite electrode material, characterized in that: include: (1) adding a metal salt to a spinning solvent, adding polyvinyl pyrrolidone, stirring to obtain a mixed sol, and then adding polystyrene microspheres, stirring to obtain a precursor sol; (2) The precursor sol is loaded into a syringe, which is fixed to a spinning machine. After the spinning parameters are set, spinning is started. After the spinning is completed, the obtained composite fiber film green body is removed from the drum, and then dried, laser sintered, and cooled to obtain a nanofiber cooked body, i.e., a nano-micron pore composite perovskite electrode material.

2. The preparation method according to claim 1, characterized in that: The metal salt in (1) includes lanthanum nitrate, strontium nitrate, cobalt nitrate, iron nitrate, cerium nitrate and gadolinium nitrate; The molar ratio of lanthanum, strontium, cobalt, iron, cerium and gadolinium in the metal salt is 0.6:0.4:0.8:0.2:0.8:0.

2.

3. The preparation method according to claim 1, characterized in that: The spinning solvent in (1) is one of a mixed solution of N,N-dimethylformamide and water, a mixed solution of dimethylacetamide and acetone, N,N-dimethylformamide, dimethylacetamide, and tetrahydrofuran; The amount of the spinning solvent in (1) is 1 to 50 mL; The amount of polyvinyl pyrrolidone used in (1) is 0.1 to 5 g.

4. The preparation method according to claim 1, characterized in that: The diameter of the polystyrene microspheres in (1) is 50 to 200 nm.

5. The preparation method according to claim 1, characterized in that: The spinning parameters in (2) are: the distance between the syringe needle tip and the roller is 18 cm, the positive and negative voltage difference is 15 kV, and the liquid pushing speed is 0.3 mL·h -1 .

6. The preparation method according to claim 1, characterized in that: The laser sintering method in (2) is to lay the composite fiber film green body flat on the sample table, turn on the power, adjust the laser intensity to 90% of the total intensity, use line scanning as the scanning method, the number of laser scans per millimeter is 25, the laser scanning speed is 100 mm / min, the height from the light source to the green body is 20 mm, scan continuously for 6 times to complete the sintering.

7. A nano-micron pore composite perovskite electrode material, characterized in that: The method is prepared by any one of claims 1 to 6.

8. The nano-micron pore composite perovskite electrode material according to claim 7, characterized in that: The chemical formula of the nano-microporous composite perovskite electrode material is La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ ; The δ is the oxygen vacancy concentration, 3-δ ranges from 0 to 3, and 2-δ ranges from 0 to 2.

9. Use of the nano-microporous composite perovskite electrode material according to any one of claims 7 to 8, characterized in that: Used in cathodes of solid oxide fuel cells.

10. Use of the electrode material according to claim 9, characterized in that: The application method is: (1) preparing an anode support by a tape casting method; (2) preparing the electrolyte layer by screen printing, and then performing primary sintering and secondary sintering on the electrolyte layer; (3) preparing the barrier layer by screen printing and then sintering the barrier layer; (4) preparing a cathode by screen printing and then sintering the cathode; (5) Assembling the anode support, electrolyte layer, barrier layer, and cathode to obtain a solid oxide fuel cell.